Experience Value as a Mediator Variable for Co-Creation Relationship on Alumni Loyalty: Using the SEM-PLS Model Approach - Muji Gunarto; Dian Cahyawati (LPPM Universitas Terbuka, 2022)
Purpose – This marketing research aimed to analyze the effect of co-creation and experience value on students loyalty as the customers of universities. Methodology – The survey was conducted on 278 alumni who came from five private universities in Palembang. The data were collected through online form from each university's alumni unit. The validity and reliability had been met. Data analysis was carried out by partial least square in structural equation model approach (SEM-PLS). Findings – The results showed that co-creation positively and significantly affected on experience value and alumni loyalty. Students who gain experience value from lectures could interact and could active on campus. High interaction among students, lectures, and campus showed a strong co-creation level and better experience value, impacting alumni loyalty to recommend and care about their alma mater. There should be provided space to build the campus through a strong alumni engagement. The more experience students have on campus, the more they care about their alma mater. Originality – This study observed the experience of alumni who were more objective in providing their perceptions because they were no problem of interest. Some researchers used students loyalty measure that was less objective because there still an interest as a student.